Increasing climate-related-energy penetration by integrating run-of-the river hydropower to wind/solar mix. (March 2016) - François, B.; Hingray, B.; Raynaud, D.; Borga, M.; Creutin, J.D.
Abstract: The penetration rate of Climate Related Energy sources like solar-power, wind-power and hydro-power source is potentially low as a result of the large space and time variability of their driving climatic variables. Increased penetration rates can be achieved with mixes of sources. Optimal mixes, i.e. obtained with the optimal share for each source, are being identified for a number of regions worldwide. However, they often consider wind and solar power only. Based on 33 years of daily data (1980–2012) for a set of 12 European regions, we re-estimate the optimal mix when wild run-of-the-river energy is included in the solar/wind mix. It is found to be highly region dependent but the highest shares are often obtained for run-of-the-river, ranging from 35% to 65% in Belarus and England. High solar shares (>40%) are found in southern countries but solar shares drop to less than 15% in northern countries. Wind shares range from 10 to 35% with the exception of Norway where it reaches 50%. These results put in perspective the optimal 60%–40% wind/solar mix currently used for Europe. For all regions, including run-of-the-river in the mix allows increasing the penetration rate of CREs (from 1 to 8% points). Highlights: Integration of run-of-the river (RoR) power in solar/wind power mix is analyzed. Integrating RoR power in solar/wind power mix increases the global penetration rate. Integrating RoR modifies the optimal share between solar- and wind-power. In Europe, optimal RoR/solar/wind energy mix is region dependent.